Social appearance anxiety, emotional regulation and quality of life in individuals with premature canities: a correlational study - Noor, Naheed; Latif, Sara; Irfan, Rida; Admin (Journal of the Pakistan Medical Association, 2022)
Objective: To examine and predict the relationship among social appearance anxiety, emotional regulation and quality of life in individuals with premature canities. Methods: The correlational study was conducted from September 2019 to February 2020 in Lahore, Pakistan, after approval from the Riphah International University, Lahore, and comprised individuals of either gender aged 15-25 years with premature canities. Social Appearance Anxiety Scale, Emotional Regulation Questionnaire and the Quality of Life Scale were used to measure the study variables. Data was analysed using SPSS 21. Results: Of the 100 subjects, 50(50%) each were males and females. The overall mean age was 19.80±3.33 years. Individuals with premature canities had significant social appearance anxiety which was positively correlated with emotional suppression. As social appearance anxiety increased, the quality of life decreased (p<0.05). Lower level of cognitive reappraisal and higher expressive suppression were linked with improved quality of life in individuals with premature canities (p<0.05). Conclusion: Social appearance anxiety, emotional regulation along with age were together found to be the predictors of quality of life. Key Words: Social appearance anxiety, Emotional regulation, Quality of life, Premature canities.